Analisa dan Perancangan Website E Recruitment Pegawai (Studi Kasus di Kantor Inspeksi BRI Padang) - Swandi, Andri (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
To create an effective recruitment effort at the BRI Padang Inspection Office requires a computerized employee recruitment and selection system. It would be even more effective if the recruitment process, such as job vacancy announcements, application submissions, and applicant calls, were conducted through a website-based online media platform. The traditional manual recruitment system using MS. Excel applications has proven ineffective in managing the increasing volume of applicants and maintaining data accuracy, leading to inefficiencies in processing time and decision-making. This research aims to design and implement an e-recruitment system that addresses these limitations while improving the overall recruitment process quality and efficiency. This methodology encompasses the research framework, starting from identifying problems, analyzing problems, determining objectives, studying literature, data collection techniques, system design, system testing techniques, to system evaluation techniques. The study employs a systematic approach combining qualitative and quantitative methods to ensure comprehensive system development. Data collection involves interviews with HR personnel, observation of existing recruitment procedures, and analysis of previous recruitment records to identify key requirements and system specifications. The implementation in the form of an e-recruitment website at the BRI Padang Inspection Office has the capability to overcome the problems that have been generated by the manual system using MS. Excel applications, which has proven ineffective. The system provides features including automated job posting, online application submission, applicant tracking, automated screening, and comprehensive reporting mechanisms. This digital transformation is expected to significantly reduce processing time, minimize human error, enhance data security, and improve the candidate experience throughout